Development of an Instrument for Measuring Student Satisfaction in Business Educational Institutions - Mihai-Florin Bacila; Marcel Ciprian Pop; Mircea Andrei Scridon; Raluca Ciornea (Amfiteatru Economic Journal, 2014)
As the number of prospective students decreases and competition intensifies, student satisfaction should be a core element of the universities' marketing strategy. Students' satisfaction is influenced by the degree to which higher education institutions meet or exceed their expectations. Higher education managers in general and business higher education managers in particular need to determine the students' level of satisfaction in order to assess their performance. This, however, is difficult to achieve because satisfaction is an abstract concept and no clear consensus exists over its definition and measurement. Although, on account of education's complexity and peculiarities, the investigation of satisfaction with educational services has been laborious, the literature review reveals a growing number of papers dealing with this issue. These papers consider the factors affecting satisfaction mostly as individual coefficients and ignore the latent relationships between constructs. However, since the determinants of partial student satisfaction simultaneously manifest in the overall satisfaction, it may be considered that an individual approach to them, would partially cover the issue being studied. For this reason, the purpose of this paper is to develop a model for measuring student satisfaction with business education services, a model which should be approached holistically and whose latent structure should be taken into account. The proposed measurement tool, based on the study of the literature, was tested on the students of a business educational institution and the results confirm the goodness-of-fit, reliability and validity of the model. The developed tool encompasses a number of factors that allow the assessment of student satisfaction with a wide range of services provided by business education institutions and relate to: educational process (syllabus, training of teaching staff, examination policy), administrative staff, admission process (information, staff), management of the faculty, image of the faculty, library, general information, cafeteria, campus climate, tutors, collaboration between faculty and business environment, international cooperation, leisure activities supported by the faculty.
Keywords: I21; M31; 330; student satisfaction; educational marketing; satisfaction measurement tool; satisfaction determinants; business educational institutions